Differences in Chemical Sexual Signals May Promote Reproductive Isolation and Cryptic Speciation between Iberian Wall Lizard Populations. (11th January 2012) - Gabirot Gabirot, Marianne Marianne; López López, Pilar Pilar; Martín Martín, José José
Abstract : Interpopulational variation in sexual signals may lead to premating reproductive isolation and speciation. Genetic and morphological studies suggest that the Iberian wall lizard, Podarcis hispanica, forms part of a "species complex" with several cryptic species. We explored the role of chemical sexual signals in interpopulational recognition between five distinct populations of Iberian wall lizards in Central Spain. Results showed that these populations differed in morphology and in composition and proportion of chemical compounds in femoral gland secretions of males. Tongue-flick experiments indicated that male and female lizards discriminated and were more interested in scents of lizards from their own area (i.e., Northern versus Southern populations), but did not discriminate between all populations. Moreover, only males from the populations that are geographically located more far away preferred scent of females from their own population. These data suggest that, at least between some populations, there may be reproductive isolation mediated by chemical signals and cryptic speciation.